PENINGKATAN PENDAPATAN KELUARGA MELALUI PERAN KKN TEMATIK POSDAYA BERBASIS MASJID DUSUN SENEPOSARI DESA BARUREJO - Mufidah Yusroh (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2018)
Increasing income can be done through family business. Family business is the way to increase family income through business done by family or even by herself/himself. Besides, it can be done out of family, that is the member of the business is as the owner. Through this business training, the first aim is to give understanding to all participants especially society in Seneposari, Siliragung about how to manage and increase their family income. Thus, the business training method was used to the participants who live in Seneposari, Siliragung accompanied by the college students of IAI Ibrahimy Genteng Banyuwangi of KKN Mosque-Based Posdaya Thematic.